Soil quality evaluation: generation and interpretation of indicators - Castillo-Valdez, Ximena; Etchevers-Barra, Jorge Dionisio; Hidalgo-Moreno, Claudia María Isabel; Aguirre-Gómez, Arturo (REVISTA TERRA LATINOAMERICANA, 2021)
Soil management practices alter its properties, especially when the energy inputs to the soil-plant system are less than the outputs, or its resilience is unable to return it to the state prior to the intervention. When the disturbances approach the tolerance limits of the soil system, factors that limit production appear. Changes can be established using quality indicators and indices. These show the direction of change over time. The objective of this work was to evaluate the current soil quality in four agricultural ejidos of Tepeaca, Puebla, Mexico, which have centuries of dedication to agricultural production. The history, the most common cropping patterns and the dominant land classes, defined with the participation of local producers, were investigated. Physical, chemical and biological properties of soils subjected to different management were analyzed and quality indicators were defined. The selection criteria for the sampling sites were the most frequent cultivation patterns as follows: (i) cut flower, (ii) continuous vegetables, and (iii) vegetables with resting period during the season with no rain. The same soils were used without management as reference. The properties selected as indicators were the following: pH, electrical conductivity, soil organic matter, wet aggregate stability, Olsen extractable phosphorus, DTPA extractable iron, and earthworm density. The first four were sensitive to differentiate between undisturbed (uncultivated) soils from cultivated soils. The last four were selected by showing rates of change according to cropping patterns, which indicates the need to promote agronomic management strategies. With these properties, a soil quality index was built that allows to establish the direction of change that soil quality will experience when modifying one or more indicators.